2022
DOI: 10.1177/23259671221078586
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Grip Strength and Return to Heavy Manual Work at a Mean 5-Year Follow-up After Arthroscopic Release of Recalcitrant Lateral Epicondylitis

Abstract: Background: Lateral epicondylitis of the elbow is a common degenerative disorder in middle-aged patients. Surgery is reserved for patients who do not respond to nonoperative treatment. Purpose: To evaluate hand-grip strength and return to heavy manual activities in patients engaged in work requiring heavy lifting after arthroscopic release of refractory lateral epicondylitis. Study Design: Case series; Level of evidence, 4. Methods: The study included consecutive patients who underwent arthroscopic release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Fahmy et al 32 also looked at the outcomes of arthroscopic releases prospectively for RLE in 22 patients engaged primarily in heavy manual occupations and a minimum of 48 months of follow-up. Highly significant improvements were found between preoperative and 1-month postoperative scores regarding handgrip strength, VAS score for pain, and MEPS (p < 0.00001 for all 3), as well as with all 3 outcome measures between 1 and 6 months (grip strength and MEPS, p < 0.00001; VAS, p = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Fahmy et al 32 also looked at the outcomes of arthroscopic releases prospectively for RLE in 22 patients engaged primarily in heavy manual occupations and a minimum of 48 months of follow-up. Highly significant improvements were found between preoperative and 1-month postoperative scores regarding handgrip strength, VAS score for pain, and MEPS (p < 0.00001 for all 3), as well as with all 3 outcome measures between 1 and 6 months (grip strength and MEPS, p < 0.00001; VAS, p = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Several determinants were reported to be associated with LET, such as working procedures characterized by the long-term repetitive forearm and hand movement [ 2 ], the excessive neuronal activity by nociceptors that derive from the radial nerve leading to axonal sprouting of the free nerve endings and peripheral sensitization, smoking habits, and metabolic factors, such as estrogen decline, hypercholesterolemia, and obesity [ 1 ]. LET is a degenerative overuse process of the extensor carpi radialis brevis and of the common extensor tendon [ 3 ] characterized by histological micro-rupture, vascular proliferation, and hyaline degeneration without inflammatory cells infiltrating within the tendon tissue [ 4 ]. The main clinical manifestation is hyperalgesia during active range of motion of the elbow and at the palpation in the lateral epicondyle area, which is exacerbated by prono-supination of the forearm [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Open surgery approaches mainly concentrated on releasing the origin of the extensor and offered long-term results [12]. The literature research showed favourable results for LE patients treated with arthroscopic surgery, patients reported to be satis ed with the operative results, but the technical requirements were high, and the signi cant improvements were found on functional measures between 1 and 6 months [13]. Cho, B. K.et al reported that the mini-open surgical procedure was an effective method for LE [14].…”
Section: Introductionmentioning
confidence: 99%